1998
DOI: 10.1136/jmg.35.11.910
|View full text |Cite
|
Sign up to set email alerts
|

Identification of 12 novel mutations in the alpha-N-acetylglucosaminidase gene in 14 patients with Sanfilippo syndrome type B (mucopolysaccharidosis type IIIB).

Abstract: Sanfilippo syndrome type B or mucopolysaccharidosis type IIIB (MPS IIIB) is one of a group of lysosomal storage disorders that are characterised by the inability to breakdown heparan sulphate. In MPS IIIB, there is a deficiency in the enzyme a-N-acetylglucosaminidase (NAGLU) and early clinical symptoms include aggressive behaviour and hyperactivity followed by progressive mental retardation. The disease is autosomal recessive and the gene for NAGLU, which is situated on chromosome 17q21, is approximately 8.5 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
41
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 14 publications
(2 reference statements)
4
41
1
Order By: Relevance
“…The amino acid substitution (p.R565L) involved a highly conserved residue, Table 2. Other mutations affecting the same amino acid were previously shown to cause MPS IIIB (Beesley et al 1998;Bunge et al 1999;Weber et al 1999). The two siblings with Batten disease had homozygous (novel) deletions involving exon 3, introns 6 and 8, and exons 11, 14, and 15 of the CLN3 gene (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…The amino acid substitution (p.R565L) involved a highly conserved residue, Table 2. Other mutations affecting the same amino acid were previously shown to cause MPS IIIB (Beesley et al 1998;Bunge et al 1999;Weber et al 1999). The two siblings with Batten disease had homozygous (novel) deletions involving exon 3, introns 6 and 8, and exons 11, 14, and 15 of the CLN3 gene (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…org), is responsible for cleaving the glycosidic bond found in the backbone of heparan and thus plays a key role in heparan recycling. More than 100 different mutations in the naglu gene have been associated with the MPS IIIB phenotype, and biochemical studies have confirmed the deleterious effects of many of these mutations (1)(2)(3)(4)(5)(6)(7)(8)(9). Despite having been cloned ÏŸ10 years ago, no structural or mechanistic data for NAGLU have been obtained, hindering the development of potential therapeutic strategies to treat patients suffering from MPS IIIB.…”
mentioning
confidence: 99%
“…Two siblings with an attenuated phenotype were compound heterozygous for R565P/F314L, and one patient with a severe phenotype was homozygous for R565P. To our knowledge, excluding Tanaka's report, 88 different mutations have been reported in 116 MPS IIIB patients, and 39 patients showed homozygous mutations Schmidtchen et al 1998;Beesley et al 1998;Bunge et al 1999;Weber et al 1999;Tessitore et al 2000). In previous reports, no apparent common mutations were identified.…”
Section: Discussionmentioning
confidence: 94%
“…Since little is known about the catalytic site and tertiary structure of the enzyme, it is very difficult to draw any conclusions on the effect of the missense mutation on enzyme function. However, two other missense mutations at Arg-565 (R565W and R565Q) have been reported in MPS IIIB patients with a severe phenotype (Beesley et al 1998;Bunge et al 1999;Weber et al 1999;Tanaka et al 2002). Arginine is positively charged and more hydrophilic than proline, which is uncharged and moderately polar (Nelson and Cox 2000).…”
Section: Discussionmentioning
confidence: 99%